Scaling big data with Hadoop and Solr : learn exciting new ways to build efficient, high performance enterprise search repositories for Big Data using Hadoop and Solr /: learn exciting new ways to build efficient, high performance enterprise search repositories for Big Data using Hadoop and Solr. (2013) - Unknown
No abstract available